The Impact of Automation on Performance and Work Processes in Shahroud University of Medical Sciences - Mohammad Amiri; Mehdi Raei; Elham Sadeghi; Shima Naderi (مجله انفورماتیک سلامت و زیست پزشکی, 2014)
Introduction: The implementation of automation is considered as a process in organizational development, and change the procedure of affairs. The aim of this paper was to determine the impact of automation on performance and work processes in Shahroud University of Medical Sciences in 2012. Method: This descriptive analytical study was conducted on 239 automation users in presidential field, deputy departments, emergency centers and hospitals of Shahroud University of Medical Sciences. The data were collected by a questionnaire contained 30 questions with five-point Likert scale which its reliability and validity had been confirmed. Data analysis performed by Chi-square and Pearson Correlation. To analyze the data SPSS version 20 was used. Results: The average of work time with automation network was 30.05±‌2.70 hours per day. Only 28% of staffs were satisfied of automation and the rest has relative satisfaction (61.9%) or were unsatisfied (10.1%). The average scores of attitudes toward automation was 64.83±-6.96and 88.3% of staffs had positive attitude, and 11.7% had a negative attitude. Also, there was significant relationship between attitude and satisfaction, as people who had more positive attitudes were more satisfied (P=0.001). Conclusion: The results indicated a positive impact of automation on the performance of employees. Due to problems in implementation and use of this technology, resolving operational problems can increase the efficiency and effectiveness of the organization.